Current techniques and procedures in paediatric and congenital cardiac catheter intervention. Issue 2 (February 2021) - Hayes, Nicholas; Ho, Andrew
Abstract: There has been marked innovation and progress in the techniques, technologies and outcomes in the field of paediatric and congenital cardiac catheter intervention over the past 4 decades. In the modern era, it is now possible to treat many forms of congenital heart disease through minimally invasive percutaneous therapies, with associated reduction in morbidity for this group of patients. This article provides an overview of current practice and developments in this field, with particular focus on the interventional procedures commonly performed in the paediatric population.